ГРАФІЧНА ПІДГОТОВКА МОЛОДШИХ ШКОЛЯРІВ НА УРОКАХ ТРУДОВОГО НАВЧАННЯ (Педагогіка вищої та середньої школи, 2004)
In the article is consideration of the question about possibility the lessons of work in taking hold junior schoolchildren of graphic literacy.